USING PICTURES IN TEACHING ENGLISH TO STUDENTS IN UZBEKISTAN - Tokumbetova Mekhribonu Shavkat qizi; Khasanova Mavluda Alisherqizi (Journals Park Publishing, 2023)
Audio-visual helps have been one of the foremost persuasive sources in educating and learning an obscure dialect. The utilization of pictures found in course readings has incredible suggestions for instructing and learning the English dialect to non-natives. The current consideration pointed to investigating the utilization of pictures in reading material to educate the English dialect in essential schools in the Uzbekistan urban setting. The analysts, taking after the standards of subjective inquiry, utilized lesson perceptions and interviews to collect information. The discoveries of the think about repeated that the utilization of pictures in dialect instructing is very supportive; in any case, the instructors beneath perception, regularly, did not make use of pictures found within the reading material to instruct the English dialect. The instructors can make their addresses and classroom exercises more enthusiastic, interesting, and productive by utilizing the pictures found within the course readings they utilize to educate the English dialect.
Keywords: Audio, visual aids, ELT, English language, Pictures, Textbooks, Young learners